Comparative transcriptomic and phenotypic analysis of monoclonal and polyclonal Populus deltoides genotypes - Gosselaar, Macy; Arick, Mark A.; Hsu, Chuan-Yu; Renninger, Heidi; Siegert, Courtney M.; Shafqat, Waqar; Peterson, Daniel G.; Himes, Austin (Frontiers in Plant Science, 2025)
Populus species are highly valued for bioenergy and bioproducts due to their rapid growth and productivity. Polyclonal plantings, or mixtures of Populus clones, have shown the potential to enhance resource utilization and productivity, likely due to phenotypic differences arising from niche differentiation. In this study, we investigated gene expression and productivity in monoclonal and polyclonal stands of P. deltoides. Phenotypic results showed that polyclonal plots exhibited higher leaf area index (LAI; p < 0.01, 2.96 ± 0.057 m2) and total biomass (p < 0.01, 2.74 ± 0.06) compared to monoclonal plots, indicating superior productivity. RNA sequencing revealed upregulation of key genes such as exocyst subunit exo70 family protein H7 (EXO70H7), NDH-dependent cyclic electron flow 5 (NDF5), and expansin-like A3 (EXLA3). We also observed enrichment in phenylalanine metabolism and other secondary metabolic pathways in clone S7C8. Phenotypic results, upregulated genes and enriched biological pathways identified in this study may explain the enhanced productivity, increased nitrate content, and expanded canopy in polyclonal plantings. Overall, this study provides a foundation for future research to enhance forest productivity by linking molecular mechanisms to practical applications in field plantings.